KARAKTER DAN ADAB DALAM PENDIDIKAN SUDUT PANDANG SYEKH AZ ZARNUJI - Pipit Pitriani; Wasehudin; Lalu Turjiman Ahmad; Wahyu Hidayat (STAI Pelabuhan Ratu, 2023)
This study aims to describe character education from Az Zarnuji's perspective. This study uses a literature study approach. In general, Sheikh Az Zarnuji's thoughts cover three things, namely: goals and intentions in learning, classification of knowledge, and methods in learning. The implementation of character education is more emphasized on goals, learning intentions and learning methods. In terms of learning methods, Az Zarnuji offers two methods, namely ethical methods and strategic methods. All of this is a form of character education put forward by Syekh Az Zarnuji in his work, namely Ta'lim Muta'allim. Keywords: Character, Az Zarnuji's perspective